Protective Effect of Aerobic Training and Royal Jelly on Cellular senescence Markers of Cardiomyocytes in Obese Rats - Iraj Hoseinzade; Ahmad Abdi; Asieh Abbassi Daloii (Shahid Beheshti University, 2022)
Background and Purpose: Fat tissue, frequently the largest organ in humans, is at the nexus of mechanisms involved in longevity and age-related metabolic dysfunction. Fat distribution and function change dramatically throughout life. Obesity is a major risk factor for development of comorbidities such as type-2 diabetes, neurological disorders, osteoarthritis, cancer, cardiovascular and renal diseases, which is associated with increased senescent cell and heart disorders. Exercise training and natural supplements constitute an indispensable, tool in the management of obesity and obesity-related disorders and can have a positive effect on longevity. However, interactive effects of aerobic training (AT) and royal jelly (RJ) is still not well understood in cellular senescence markers of cardiomyocytes in high fat diet (HFD) rats. Therefore, this study aimed to investigate the protective effect of AT and RJ on p16 and p21of cardiomyocytes in obese rats.Material and Methods: In this experimental study, 45 male Wistar rats were randomly divided into five groups (n=9): Normal Diet (ND), High Fat Diet (HFD), High Fat Diet-Training (HFDT), High Fat Diet-Royal Jelly (HFDRJ) and High Fat Diet-Training-Royal Jelly (HFDTRJ). HFD induction was performed using a high-fat diet containing 17% protein, 43% carbohydrate and 40% fat. The supplement groups received 100 mg of royal jelly (per kg of body weight) diluted in distilled water orally during the intervention period. Aerobic exercise program including running on the treadmill with an intensity of 50-60% maximal oxygen consumption (VO2max), was performed five days a week for eight weeks. 48 hours after the last training session, rats were anesthetized with a combination ketamine and xylazine, and after extraction, the heart tissue was placed in a nitrogen tank and sent to the laboratory to measure p16 and p21 gene expression levels.  p16 and p21 gene expression levels were measured by real-time PCR. Data were analyzed by two-way analysis of variance and Tukey post hoc test at the P £ 0.05.Results: HFD significantly increased the expression of p16 (P = 0.000) and p21 (P = 0.000). Data analysis using two-way analysis of variance showed that AT and RJ significantly reduced the expression of p16 (P = 0.000 and P = 0.000, respectively) and p21 (P = 0.000 and P = 0.000, respectively) cardiomyocytes in HFD rats. However, the interaction of AT with RJ had no significant effect on the expression of p16 (P = 0.989) and p21 (P = 0.870) cardiomyocytes in HFD rats.Conclusion: HFD in rats increased p16 and p21and AT and RJ improved the expression of aging-related genes in cardiomyocytes of HFD rats; however, the interaction of AT and RJ had no effect on cellular aging markers. These data indicate that obesity is associated with increased of cellular senescence markers, and AT and RJ as an appropriate therapeutic intervention in HFD animals, it can delay cellular aging. Further investigation is needed for the interactive effect of the AT and RJ.